The Influence Of Human Resources Competence, Organizational Culture Influence And Transformational Leadership Style On Employee Performance Through Employee Job Satisfaction As Intervening Variable At Pdam Tirtanadi Medan - Rizki Aulia, Muhammad; Pakpahan, Efendy; Krisna Marpaung, Fenny (International Journal of Science, Technology & Management, 2022)
This study aims to find out whether human resource competence has an indirect effect on employee performance through job satisfaction, to find out whether organizational culture has an indirect effect on employee performance through job satisfaction and to find out whether transformational leadership style has an indirect effect on employee performance through job satisfaction. . Descriptive statistics are statistics that function to describe or provide an overview of the object under study through sample data or the population as it is, without analyzing and making conclusions that apply to the public. The influence of human resource competence on job satisfaction through employee performance is 0.008, with a T statistic value of 0.439 (> 1.993) and a significance value (p-values) of 0.661 (< 0.05). Thus, the first hypothesis (H8) in the study this is rejected. The influence of Organizational Culture on job satisfaction through employee performance is 0.459, with a T statistic of 02.447 (< 1.993 and a significance value (p-values) of 0.015 (> 0.05). Thus, the second hypothesis (H9) in this study is accepted. The effect of transformational leadership style on job satisfaction through employee performance is 0.098, with a T statistic of 2.242 (>1.993 and a significance value (p-values) of 0.025 (<0.05) thus, the third hypothesis (H10) in this study is accepted.